Identification of the fungi causing onychomycosis to fish traders in the fish market Lhokseumawe city Pusong - M.Raisya Kesha; Juwita Sahputri; Wizar Putri Mellaratna (Jurnal EduHealth, 2024)
Onychomycosis is a disease caused by dermatophyte fungi, including Microsporum, Trichophyton and Epidermophyton, apart from that, there are also non-dermatophyte fungi, including Aspergillus sp., and Malessezia furfur. This study aims to identify dermatophyte and non-dermatophyte fungi in the toenails of fish traders at the Pusong Fish Market and identify factors that can increase the risk of fungal infections in the toenails of fish traders, such as sanitation conditions, personal hygiene, or other environmental factors. This research uses a descriptive method by taking nail samples from fish traders, then analyzing them using Sabouraud Dextrose Agar (SDA) culture media. The results of the study showed that 100% of the samples showed nail abnormalities, with the distribution of non-dermatophyte fungal infections reaching 63.2% consisting of 24 people and dermatophyte 36.8% consisting of 14 people. Based on risk factor analysis, it indicates that sanitation conditions and personal hygiene of fish traders play an important role in the spread of fungal infections. The conclusion of this research is that all fish traders at the Pusong market experienced nail disorders (Onychomycosis) due to being infected with dermatophyte and non-dermatophyte fungi with the most common type of fungus being Aspergillus Niger which is a non-dermatophyte fungal group.